Survival of Rhizoctonia solani in soil under varying temperature regimes - A.P. SINHA, PRATIBHA SATI and (Indian Phytopathology, 2002)
The survival of mycelia and sclerotia of R. solani at various temperature regimes was studied. Diseased leaf sheaths were placed in nylon bags and buried in natural soil. Samples were tested for the viability of the pathogen after incubation under different temperatures. The fungus survived in infected plant debris for up to 150 d, and in the form of sclerotia it survived until the next crop season. Increasing storage time reduced the survival of the pathogen. Mycelium survived at 10-40deg C for 150 din infected crop debris, and for 120 d at 0degree C. Constant exposure at 40degree C resulted in reduced survival of the fungus. In the form of sclerotia, R. solani survived for 330 d at different temperatures. Survival of the sclerotia was low at 0 and 40degree C, whereas at 10 and 28degree C the survival was better. It is suggested that the pathogen, in the form of sclerotia, was good enough for the transmission to the next crop season.